Demonstration of two-laser Polarimeter-Interferometer (PIer) scheme for simultaneous measurements of Faraday rotation angle and electron density on HL-2A. (6th November 2017) - Li, Y.G.; Zhou, Y.; Deng, Z.C.; Li, Y.; Wang, H.X.; Yuan, B.S.; Yi, J.; Yin, Z.J.; Ji, X.Q.; Wu, T.Y.; Chen, W.J.; Chen, W; et al.
Abstract: A novel two-laser P olarimeter- I nterferomet er ( PIer ) diagnostic scheme, in which Faraday rotation angle ( α F ) and electron density ( n e ) can be simultaneously measured by taking advantage of two lasers and two detectors for each channel, has been successfully demonstrated on HL-2A tokamak through upgrading one channel of existing monofunctional Faraday-effect polarimeter. In comparison with the conventional three-laser PIer diagnostic, two-laser PIer generates only one intermediate frequency (IF), avoiding the overlap of IF frequency bands, so as to increase the time resolution and decrease the phase noise of system. The single channel two-laser PIer was firstly put into operation in 2016 HL-2A experimental campaign, and both Faraday rotation angle and electron density phase have been measured with a fast time resolution of 1.0 μ s and a phase resolution of 0.1 ̂ and 1.0 ̂, respectively. This work is valuable for next step far-infrared (FIR) laser PIer construction on HL-2M tokamak, as well as the future International Thermonuclear Experimental Reactor (ITER).